Psychiatric Disease after Isolated Traumatic Upper Extremity Amputation - Shue, Shirley; Wu-Fienberg, Yuewei; Chepla, Kyle J. (Journal of Hand and Microsurgery, 2020)
Introduction Psychiatric disease after traumatic limb loss impacts rehabilitation, prosthesis use, and quality of life. The purpose of this study was to evaluate the prevalence of psychiatric disease in civilians after isolated, traumatic upper extremity amputation and determine if any risk factors are associated with developing psychiatric disease.Materials and Methods Demographics, time since injury, mechanism of injury, amputation level, hand affected (dominant vs. nondominant), Bureau of Workers’ Compensation (BWC) status, and prosthesis use were retrospectively reviewed for all patients treated from 2012 to 2017. For patients with an International Statistical Classification of Diseases and Related Health Problems, 10th revision (ICD-10) diagnosed psychiatric disease, the diagnosis and length of treatment were recorded. Patients were grouped by presence or absence of psychiatric diagnosis and data analysis was performed using descriptive statistics, Fisher’s exact test, and relative risk.Results Forty-six patients met the inclusion criteria. Thirty-one patients (67.4%) had at least one diagnosed psychiatric condition. Major depressive disorder was the most common (n = 14), followed by posttraumatic stress disorder (n = 11), adjustment disorder (n = 11), anxiety (n = 6), and panic disorder (n = 2). No statistically significant correlation was seen between psychiatric illness and gender, age at the time of injury, time since injury, current employment status, BWC status, hand injured (dominant vs. nondominant), prosthetic use, or level of amputation.Conclusion The rates of depression and anxiety after traumatic upper limb loss in the civilian population are similar to reported rates after combat injury. While we were unable to identify a statistically significant association with any of the studied variables, upper extremity surgeons should be aware of the high prevalence of psychiatric disease after traumatic upper extremity amputation.
Keywords: amputation; farm; prevalence; psychiatric; traumatic